2011
DOI: 10.1590/s1807-59322011000900012
|View full text |Cite
|
Sign up to set email alerts
|

Is allergic rhinitis a trivial disease?

Abstract: BACKGROUND:Asthma and rhinitis often coexist, which potentially increases the disease severity and can negatively impact a patients' quality of life. However, there are few reports based on data obtained from the International Study of Asthma and Allergies in Childhood examining asthma severity in combination with rhinitis-related symptoms.OBJECTIVE:To demonstrate whether current rhinitis and current rhinoconjunctivitis are associated with the development of asthma or its increasing severity in Brazilian adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 35 publications
2
6
0
3
Order By: Relevance
“…Nevertheless, in future manuscripts, multiple logistic analyses will be applied to evaluate risk factors, to confirm these findings and to compare specific symptoms such as cough. The importance of this increase in sensitization has been reported in previous studies demonstrating the progression from sensitization to conjunctivitis and rhinitis, as well as asthma (6,18,21,22). …”
Section: Discussionsupporting
confidence: 62%
“…Nevertheless, in future manuscripts, multiple logistic analyses will be applied to evaluate risk factors, to confirm these findings and to compare specific symptoms such as cough. The importance of this increase in sensitization has been reported in previous studies demonstrating the progression from sensitization to conjunctivitis and rhinitis, as well as asthma (6,18,21,22). …”
Section: Discussionsupporting
confidence: 62%
“…Analyzing Brazilian data obtained in ISAAC Phase III in Brazilian adolescents, it was found that the association between asthma and rhinitis was high (r=0.82), as well as with rhinoconjunctivitis (r=0.75). The presence of current rhinitis and rhinoconjunctivitis was associated with increased risk of developing asthma and severe asthma ( 54 ) . This fact becomes more evident when atopic dermatitis is associated with rhinitis ( 55 ) .…”
Section: Isaac Phase IIImentioning
confidence: 99%
“…Nevertheless, it has been shown that: 1) In the LARGE multicenter study, asthmatics with Arg/Arg homozygous genotype, receiving inhaled corticosteroids, experience no change in hyperresponsiveness status even when long acting β2 agonists were used 8 ; 2) a combination of salmeterol plus inhaled corticosteroid in the patients Gly/Gly, at amino acid 16 increased 2.4 times the PC20, resulted in decreased bronchial hyperresponsiveness 5,8 ; 3) the Gly16/Gln27 haplotype was inversely associated with hyperresponsiveness to methacholine, while the Arg16/Gln27 haplotype was associated with a greater degree of hyperresponsiveness 9 , and 4) children homozygous and heterozygous for Arg16 had higher bronchodilator responses than Gly16 homozygotes patients 10 . These findings correspond to Caucasians, however, in Venezuela there is a high prevalence of asthma and a large Mestizo population which seem to have a high genetic segregation [11][12][13] . The relevance of these polymorphisms in various populations and its clinical relevance so far are unknown 2 .…”
Section: Introductionmentioning
confidence: 67%